2021
DOI: 10.3389/fpsyg.2021.710636
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Everyday Ecologies: Principles for Manual Annotation of Many Hours of Infants' Lives

Abstract: Everyday experiences are the experiences available to shape developmental change. Remarkable advances in devices used to record infants' and toddlers' everyday experiences, as well as in repositories to aggregate and share such recordings across teams of theorists, have yielded a potential gold mine of insights to spur next-generation theories of experience-dependent change. Making full use of these advances, however, currently requires manual annotation. Manually annotating many hours of everyday life is a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 96 publications
0
14
0
Order By: Relevance
“…Prompts for greater fidelity to properties of everyday time include favoring continuous time instead of "trial" units (Huk, Bonnen, & He, 2018), instantiating slower rates of switching between instances (Duncan & Schlichting, 2018), investigating extended timescale dynamics (Creel, 2019;Halpern & Bartlett, 2010;Naselaris, Allen, & Kay, 2021;Spencer, Perone, & Buss, 2011;Vlach, 2019), and connecting multiple scales of integrating information over time (Hasson et al, 2015;Thelen & Smith, 1994). Sampling extended timescales of everyday life is a foundational step en route to better aligning empirical protocols with everyday temporal realities in part because it affords discoveries about multiple timescales (Mendoza & Fausey, 2021b;Ritwika et al, 2020). The everyday parameters discovered here propel theorists toward testing hypotheses in which learners encounter many opportunities to integrate musical episodes over seconds mixed with some opportunities to integrate over hours.…”
Section: Everyday Parametersmentioning
confidence: 98%
See 1 more Smart Citation
“…Prompts for greater fidelity to properties of everyday time include favoring continuous time instead of "trial" units (Huk, Bonnen, & He, 2018), instantiating slower rates of switching between instances (Duncan & Schlichting, 2018), investigating extended timescale dynamics (Creel, 2019;Halpern & Bartlett, 2010;Naselaris, Allen, & Kay, 2021;Spencer, Perone, & Buss, 2011;Vlach, 2019), and connecting multiple scales of integrating information over time (Hasson et al, 2015;Thelen & Smith, 1994). Sampling extended timescales of everyday life is a foundational step en route to better aligning empirical protocols with everyday temporal realities in part because it affords discoveries about multiple timescales (Mendoza & Fausey, 2021b;Ritwika et al, 2020). The everyday parameters discovered here propel theorists toward testing hypotheses in which learners encounter many opportunities to integrate musical episodes over seconds mixed with some opportunities to integrate over hours.…”
Section: Everyday Parametersmentioning
confidence: 98%
“…These details can be annotated together with details of nonmusical episodes like linguistic exchanges and naps in order to advance theories of experience-dependent change that respect the rich nature of infants' everyday soundscapes (Warlaumont, Sobowale, & Fausey, 2022). We encourage theorists to collectively make progress by annotating the shared everyday recordings (Mendoza & Fausey, 2018;2021a;2021b).…”
Section: Toward More Expansive Everyday Parametersmentioning
confidence: 99%
“…Some heroic efforts to annotate daylong data in more detail have demonstrated both the richness of what could be studied were it manually annotated (e.g., Montag, 2020) and the potential drawbacks of relying exclusively on automated output (e.g., Ferjan Ramírez et al, 2021). Encouragingly, protocols and guides for manually annotating daylong data have started to emerge, some with an eye toward maximizing efficiency (Casillas, Bergelson, et al, 2017;Cychosz et al, 2021;Mendoza & Fausey, 2021). Researchers choosing this path can expect large investments of time and money (see Figure 1).…”
Section: Capturing Language In Recordingsmentioning
confidence: 99%
“…In the past two decades, there has been a surge in naturalistic work in developmental psychology (Yoshida and Smith, 2008;Adolph, 2016;Bulgarelli and Bergelson, 2020;Sullivan et al, 2021) which has yielded several insights into the design and interpretation of naturalistic data. For example, researchers have shown that first-person view head cameras provide a more valid recording of what infants are visually attending to in their environment than traditional third-person recordings (Yurovsky et al, 2013), and others have examined assumptions embedded in hour-long vs. full day recordings (Bergelson et al, 2019; see Mendoza and Fausey, 2021b, for an introduction to thinking through decisions surrounding who, what, where, and how to build and code large, naturalistic corpora). Here, we give recommendations specific to studying the early language and music environment in tandem, from a developmentalecological perspective.…”
Section: Recommendations For Conducting Developmental-ecological Rese...mentioning
confidence: 99%